2013
DOI: 10.1249/mss.0b013e318299afd4
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity and Lower Limb Lymphedema among Uterine Cancer Survivors

Abstract: Purpose Physical activity (PA) is known to provide physical and mental health benefits to uterine cancer survivors. However, it is unknown if PA associates with lower limb lymphedema (LLL), an accumulation of protein-rich fluid in the lower limbs. Therefore, we sought to examine the association between PA and LLL in uterine cancer survivors, with a focus on walking. Methods We conducted a cross-sectional study using mailed surveys among uterine cancer survivors who received care at a university-based cancer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
1
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 49 publications
3
34
1
3
Order By: Relevance
“…Women who self-reported higher levels of daily walking were marginally more likely to be retired ( P =0.07), and have lower BMI ( P =0.06; data not shown). Demographic and clinical characteristics associated with LLL have been reported previously [5]. …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Women who self-reported higher levels of daily walking were marginally more likely to be retired ( P =0.07), and have lower BMI ( P =0.06; data not shown). Demographic and clinical characteristics associated with LLL have been reported previously [5]. …”
Section: Resultsmentioning
confidence: 99%
“…For each participant, an aggregate measure of MET-hrs·wk −1 was created by summing the MET-hrs·wk −1 for each activity described by the participant. We created categories of MET-hrs·wk −1 , defined as <3.0, 3.0–8.9, 9.0–17.9, and ≥18.0 that correspond to <1.0, 1.0–2.9, 3.0–5.9, and ≥6.0 hours per week of moderate-intensity PA, consistent with prior analyses among uterine cancer survivors [5]. Participants were asked to report how many blocks they walked on an average day during the past year.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Participation in higher levels of physical activity or in walking was associated with reduced lymphedema. 35 Another qualitative study that was conducted among GCSs who were involved in a home-based physical activity efficacy trial 36 found that participants experienced several benefits, including psychological well-being, physical fitness, and improved functioning. Our findings also are consistent with a previous report that positively associated the availability of emotional support with physical activity.…”
Section: Discussionmentioning
confidence: 99%